Post-COVID-19 Otolaryngological Manifestations: The Review - Kandefer, Tomasz; Sroka, Maria; Walkowski, Radosław Jan; Barański, Marcin; Klonowska, Justyna; Kosek, Szymon; Wasiniewska, Weronika (Quality in Sport, 2025)
The World Health Organization defines Post-COVID-19 syndrome as the continuation or development of new symptoms occurring at least 3 months after initial SARS-CoV-2 infection, lasting for at least 2 months and unexplainable by alternative diagnoses. Meta-analyses estimate a pooled global Post-COVID-19 prevalence of 36% among COVID-19 positive individuals, with geographic variations and persistence of symptoms even at 1-2 year follow-up. The pathophysiology of otolaryngological manifestations involves multiple mechanisms: damage to non-neuronal cells in the olfactory epithelium via ACE2 and TMPRSS2 receptors for smell disorders; microvascular damage, direct viral invasion, and inflammatory responses for audiovestibular symptoms; and direct viral impact, vagus nerve neuropathy, and systemic inflammation for upper airway and voice disorders. Management strategies include olfactory training for smell disorders (57% improvement with adherence), hearing aids and vestibular rehabilitation for audiovestibular symptoms, and voice therapy and pharmaceutical interventions for dysphonia. This review synthesizes current knowledge on Post-COVID-19 otolaryngological manifestations and identifies knowledge gaps in pathophysiological mechanisms and optimal treatment approaches, highlighting the need for standardized assessment protocols, longer-term follow-up studies and establishment of evidence-based multidisciplinary care protocols through controlled clinical trials.